Encaje bancario y su impacto en el margen de intermediación de Colombia del 2000 al 2016 (2017)
"This paper tries to determine the relation between the lace rate established by the central bank and its effect over the margin of intermediation that the banks obtain. There are many academical studies abiut the role of this rate on the countries economies, which is not only a financial regulatory measure, it is also a monetary instrument that complements the adjustment established by the interest rate.Based on previous models, financial data is introduced on a econometric analysis to evaluate the impact on the interest rates established by the banks." -- Tomado del Formato de Documento de Grado.